The organization and operation of the educational inspection in Ceuta. The general plan of action 2013-2017. Some general considerations - López Ruiz, Mª del Carmen (Avances en Supervisión Educativa, 2014)
Contribute to the improvement of the educational establishments, the coexistence and academic results constitute the main reason of the inspection task. The educational Inspection in Ceuta, part of the Office of Inspection of the MECD is based on its consideration as the most important factor to improve the quality of education, focusing their performances in the schools, the teaching role and leadership roles. In this article, we will briefly describe the organization and operation of the educational inspection in Ceuta while some general considerations are offered on the General Plan of Action for the four-year period 2013-2017, supplemented by the Annual Plan of Activities in the current academic year 2014-2015.